Chemical characterization of gaseous species from the pyrolysis process using scrap tires - S. Pongnailert; T. Supadit; P. Poungsuk; S. Pongpiachan (My University, 2013)
Particle exposure can lead to a variety of health effects.For example, numerous studies link particle levels to increased hospital admissions and emergency room visits -and even to death from heart or lung diseases.Scrap tire combustion releases several toxic air pollutants.This study assessed the generation of H 2 , N 2 , CO, H 2 S and nine aliphatic compounds, namely CH 4 (Methane), C 2 H 2 (Acetylene), C 2 H 4 (Ethylene), C 2 H 6 (Ethane), C 3 H 6 (Propylene), C 3 H 8 (Propane), C 4 H 8 (Butene), C 4 H 10 (Butane), C 5 H 12 (Pentane) generated in a used-tire pyrolysis process and the aliphatics removal by a wet scrubber (WSB) and a flare.CH 4 , H 2 , N 2 and C 2 H 6 were found to be major gaseous species in pyrolysis emissions with the percentage contributions to total sum of gaseous species of 33.18%, 15.62%, 12.23% and 8.69% respectively.
Keywords: Propane; Scrap; Butane; Acetylene; Toxic Organic Pollutants Impact